THE TRANSFER OF MODALIZATION IN THE INDONESIAN TRANSLATION OF ENGLISH INTERPERSONAL CLAUSES - Mujiyanto, Yan (Language Circle: Journal of Language and Literature, 2010)
This study aims to provide explanation on the fransfer of modalization in restructuring interpersonal clauses.As a case study, it has been deliberately directed to analyze written clauses in English texts and theircounterparts in Indonesian. Four major procedures were taken to manage the data withdrawn from thetexts, i.e. (1) data reduction, (2) data display, (3) data analysis, dan (4) inferencing. Based on theprocedures, it was found that in order to achieve functional equivalence, interpersonal clauses weretranslated by means of restructuring processes. The grammar of proposition has been restructured in threemajor modes, i.e. (1) the translation of polarity which includes affirmative, polar interrogative, whinterrogative,and exclamative restructuring , (2) the restructuring of probability which includes the transfer ofModal adjunct, Mood adjunct, and Grammatical metaphor, (3) the transfer of usuality which was restructuredaccording its different degrees.